2013
DOI: 10.1002/wcm.2452
|View full text |Cite
|
Sign up to set email alerts
|

Service‐based high‐speed railway base station arrangement

Abstract: To provide stable and high data rate wireless access for passengers in the train, it is necessary to properly deploy base stations along the railway. We consider this issue from the perspective of service, which is defined as the integral of the time-varying instantaneous channel capacity. With large-scale fading assumption, it will be shown that the total service of each base station is inversely proportional to the velocity of the train. Besides, we find that if the ratio of the service provided by a base st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Formally, channel service is defined as S(t) = t2 t1 C(τ )dτ for a time period of (t 1 , t 2 ), where C(τ ) is the instantaneous capacity over the channel. Based on this metric, the authors in [4] and [5] investigated the total channel service of the train and applied the proposed dominant ratio to the BS deployment. Quality of service (Qos)-based achievable rates was also investigated in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Formally, channel service is defined as S(t) = t2 t1 C(τ )dτ for a time period of (t 1 , t 2 ), where C(τ ) is the instantaneous capacity over the channel. Based on this metric, the authors in [4] and [5] investigated the total channel service of the train and applied the proposed dominant ratio to the BS deployment. Quality of service (Qos)-based achievable rates was also investigated in [6].…”
Section: Introductionmentioning
confidence: 99%
“…From the view of practical applications, [3,[17][18][19][20][21] consider the moving agent when energy harvesting happens. When the energy harvested from environment is consecutive, channel service becomes a more suitable performance metric as [19] considered. Literature [20] gives feasibility to such continuous scene.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, fixed transmit power is the simplest strategy for power allocation in HSRs. In [7], it analyzed the system service in HSRs under fixed transmit power, where some base station deployment strategies were obtained. However, it has been already demonstrated that fixed transmit power is not a good choice unless in time-invariant additive white Gaussian noise channel (AWGN) [8].…”
Section: Introductionmentioning
confidence: 99%